2022
DOI: 10.1155/2022/1286419
|View full text |Cite|
|
Sign up to set email alerts
|

A Comparative Study between Proximal Femoral Locking Plate and Multiple Cannulated Screws for Fixation of Femoral Neck Fractures in Young Adults

Abstract: Objective. To compare the clinical effect of proximal femoral locking plate (PFLP) versus multiple cancellous screw (MCS) for FNF. Methods. FNF patients were treated with the PFLP implant or multiple cancellous screws (MCSs). Patient has been followed up for at least 12 months after surgery nonunion, and the occurrence of complications, femoral neck shortening, fracture healing time, and Harris hip score were recorded and compared. Results. 77 FNF patients were treated with the PFLP (36 patients) or MCS (41 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In FNFs, subcapital and midcervical fracture types are common, and are mostly treated by arthroplasty, especially in elderly patients. In contrast, basicervical FNFs (1.8-7.6% of all PFFs) [4,8] and higher displaced fractures in the midcervical area in young patients are treated with cephalomedullary nails, dynamic hip screws, or cancellous screws [4,5,8,9]; thus, the best method is still under discussion [10]. While postoperative malrotation in the subtrochanteric region is a common and well-known problem [11][12][13], malrotation after osteosynthesis in FNFs, especially in the basicervical region, is less often described [7,14].…”
Section: Introductionmentioning
confidence: 99%
“…In FNFs, subcapital and midcervical fracture types are common, and are mostly treated by arthroplasty, especially in elderly patients. In contrast, basicervical FNFs (1.8-7.6% of all PFFs) [4,8] and higher displaced fractures in the midcervical area in young patients are treated with cephalomedullary nails, dynamic hip screws, or cancellous screws [4,5,8,9]; thus, the best method is still under discussion [10]. While postoperative malrotation in the subtrochanteric region is a common and well-known problem [11][12][13], malrotation after osteosynthesis in FNFs, especially in the basicervical region, is less often described [7,14].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%